Peningkatan Akses Usaha Mikro Kecil Menengah Berbasis Pendampingan Inovasi dan Kolaborasi di Kabupaten Majalengka - Teni Novianti (Indonesian Journal of Social Science, 2025)
The MSME mentoring program has been designated by the Governor of West Java as one of the superior programs to achieve West Java's Inner and Inner Champion through innovation and collaboration. The problems faced by several MSMEs in Majalengka Regency are limited access to permits and marketing access. Therefore, there is a need for synergy efforts based on innovation and collaboration to encourage MSMEs to increase business access. This research aims to determine the increase in business access after providing assistance to the innovation and collaboration-based MSME program in Majalengka Regency. The research method was carried out by means of innovation and collaboration-based assistance, carried out on assisted business actors who were participants in the 2023-2024 West Java Provincial Cooperative and Small Business Service MSME program, totaling 50 MSMEs in Majalengka Regency. Through this research activity, the results obtained from assisting MSMEs through the synergy of innovation and collaboration can increase business access through licensing by 80%, increase marketing by 64% and recover from the pandemic by 82%.